Properties of magnetized neutral pions at zero and finite temperature in nonlocal chiral quark models - Gomez Dumm, Daniel Alberto (2020)
The behavior of π0 meson properties in the presence of a uniform external magnetic field is studied in the context of a nonlocal extension of the Polyakov-Nambu-Jona-Lasinio model. The analysis includes the π0 mass, the effective π0-quark coupling and the pion-to-vacuum hadronic form factors, both at zero and finite temperature. Numerical results are compared with previous calculations carried out within the local NJL model, when available. The validity of chiral relations and the features of deconfinement and chiral symmetry restoration transitions are discussed.